Analysis of drosophila stress resistance at pharmacological inhibition of prostaglandins metabolism - Gorenskaya, О.; Titova, А.; Horenskyi, H. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Inhibition of inflammatory processes in the model organisms using non-steroidal anti-inflammatory drugs (NSAIDs) can be an effective geroprotective method. The mechanisms of NSAIDs action in insects have not been studied enough. It is assumed that they are similar to those in mammals and are based on the inhibition of cyclooxygenase 2, which leads to a decrease in the synthesis of prostaglandins. Prostaglandins are central signaling molecules for mediated coordinated cellular immunity of insects and control the imago eclosion, egg production and oogenesis of Drosophila. Obviously, signaling pathways exist where the role of prostaglandins has not yet been shown. In our work, the resistance to starvation of Drosophila melanogaster of wild type stock Canton-S under pharmacological inhibition of prostaglandin metabolism at different stages of ontogenesis was analyzed. In the experiments, nimesulide was used in three different concentrations – 0.1, 0.05, and 0.025 mg/ml. The results of the experiments have shown, that the development of larvae in the medium containing NSAID nimesulide leads to a decrease in resistance to stress factor – starvation on average by 19.2% in females and by 7.4% in males. Resistance to starvation of the most stress-resistant (10% of individuals with the longest life span) females decreases during the development of larvae in the medium containing nimesulide in concentrations 0.1 and 0.05 mg/ml. The consumption of nimesulide by imago at a concentration of 0.025 mg/ml during the first days of life increases stress resistance and life span at starvation in females by 12.4% and in males in all variants of the experiment on average by 17.8%. Under the same experimental conditions, life span during starvation increased in the most stress-resistant females Canton-S. Thus, pharmacological inhibition of prostaglandin metabolism leads to an increase of resistance to starvation if virgin adults are exposed to nimesulide during the first day after eclosion, and stress resistance decreases if nimesulide is consumed by larvae. This is obviously, due to that somatic tissues of the adult flies are almost entirely composed of postmitotic cells, while intensive processes of cell division are characteristic of growing larvae. The data obtained indicate that the action of nimesulide on postmitotic imago cells promotes transition of cells to increased stress tolerance, while the impact on actively dividing cells of larvae leads to a decrease in the resistance of the adults.